2023
DOI: 10.1186/s12906-023-03870-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of indigenous Pakistani honey against extensively drug-resistant clinical isolates of Salmonella enterica serovar Typhi: an alternative option to combat antimicrobial resistance

Abstract: Background Extensively drug-resistant (XDR) Salmonella enterica serovar Typhi (S. Typhi) poses a grave threat to public health due to increased mortality and morbidity caused by typhoid fever. Honey is a promising antibacterial agent, and we aimed to determine the antibacterial activity of honey against XDR S. Typhi. Methods We isolated 20 clinical isolates of XDR S. Typhi from pediatric septicemic patients and determined the minimum inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition, a study was conducted on the indigenous honey against XDR-S. Typhi strains in Pakistan revealed that Beri honey exhibited the greatest zone of inhibition, measuring between 7 and 15 mm, while Neem honey had a zone of inhibition ranging from 7 to 12 mm. The MIC and MBC of beri honey against 15% of XDR-S. Typhi isolates were determined to be 3.125% and 6.25%, respectively (Ejaz et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study was conducted on the indigenous honey against XDR-S. Typhi strains in Pakistan revealed that Beri honey exhibited the greatest zone of inhibition, measuring between 7 and 15 mm, while Neem honey had a zone of inhibition ranging from 7 to 12 mm. The MIC and MBC of beri honey against 15% of XDR-S. Typhi isolates were determined to be 3.125% and 6.25%, respectively (Ejaz et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The manuka honey (Watson & Son, New Zealand) (250g) with + 24 UMF (unique manuka factor) with MGO was commercially purchased. The honey was serially diluted at the concentrations of 10%, 20%, 30%, 40%, 50%, and 100% as described previously (Ejaz et al 2023). In short, the bacterial suspension (0.5McFarland) was evenly spread onto Muller Hinton Agar (MHA) plates.…”
Section: Molecular Detection Of Args In S Typhimentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activities were investigated by performing the broth dilution method. 53 Concentrations of the investigated compounds were in the range of 25–0.0195 mg ml −1 . The minimal inhibitory concentration (MIC) was established using 96-well microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
“…This research provides valuable insights into the antimicrobial properties of Qinling Apis cerana honey against Salmonella Typhimurium and its antibacterial mechanism. Ejaz et al, (2023) isolated 20 highly drug-resistant Salmonella Typhimurium strains from pediatric sepsis patients. PCR was used to identify the antimicrobial resistance genes carried by these strains.…”
Section: Antimicrobial Effects Of Honey On Salmonellamentioning
confidence: 99%